The Theme of Sabbath in the Bible: A Biblical Theology Approach - WANG, Donald (中国基督教研究（ISSN：3068-479X）, 2025)
The theme of Sabbath is an important area of overlooked research. This paper focuses on the theme of Sabbath. My thesis is that the theme of Sabbath develops, progresses, intensifies in the Old Testament, and how is ultimately fulfilled in Jesus Christ in the New Testament, especially in Matthew 11:28-30 and Hebrews 3-4.